Behaviour of the iron vapour core in the arc of a controlled short-arc GMAW process with different shielding gases - Wilhelm, G; Kozakov, R; Gött, G; Schöpp, H; Uhrlandt, D (Journal of physics. D, Applied physics, 2012)
The controlled metal transfer process (CMT) is a variation of the gas metal arc welding (GMAW) process which periodically varies wire feeding speed. Using a short-arc burning phase to melt the wire tip before the short circuit, heat input to the workpiece is reduced. Using a steel wire and a steel workpiece, iron vapour is produced in the arc, its maximum concentration lying centrally. The interaction of metal vapour and welding gas considerably impacts the arc profile and, consequently, the heat transfer to the weldpool. Optical emission spectroscopy has been applied to determine the radial profiles of the plasma temperature and iron vapour concentration, as well as their temporal behaviour in the arc period for different mixtures of Ar, O2 and CO2 as shielding gases. Both the absolute iron vapour density and the temporal expansion of the iron core differ considerably for the gases Ar + 8%O2, Ar + 18% CO2 and 100% CO2 respectively. Pronounced minimum in the radial temperature profile is found in the arc centre in gas mixtures with high Ar content under the presence of metal vapour. This minimum disappears in pure CO2 gas. Consequently, the temperature and electrical and thermal conductivity in the arc when CO2 is used as a shielding gas are considerably lower.